Poverty Dynamics and the Fundamental Root Causes in Iran - Zahra Azari; Parviz Mohamadzadeh; Davoud Behboudi (پژوهشهای اقتصادی)
Aim and Introduction The importance of poverty and dealing with that is so critical that poverty alleviation is the first goal in the Millennium Development Goals (MDGs) and the United Nations Sustainable Development Goals (SDGs). Therefore, it is essential to be aware of the poverty dynamics and the mechanisms involved to influence such parameters. The purpose of this research is to identify the factors affecting poverty in Iran and analyzing the interactive mechanisms of the factors that cause poverty in the country. This study emphasizes the fact that knowing the factors affecting poverty and the mechanisms of influencing these factors can have a significant impact on alleviating poverty. Methodology The current study is applied research in terms of purpose, and analytical-exploratory research in terms of information analysis. The data collection tool is semi-structured and in-depth interviews. Since the purpose of this study is to identify the factors affecting poverty in Iran from the point of view of experts on Iran's economic, social and political issues, the samples were selected and interviewed using theoretical sampling under the snowball method. By conducting 16 interviews, the research reached theoretical saturation. In order to ensure that the subsequent interviews do not add new information to the previous findings, 4 more interviews were conducted, but no new information was added to the previous findings. Therefore, theoretical saturation was ensured by conducting 20 interviews and the target study sample was 20 cases. After identifying experts and conducting deep and semi-structured interviews, thematic analysis method was applied. This analysis is the process of identifying themes in qualitative data. In this method, a suitable conceptual model is obtained using qualitative data obtained from interviews. It should be noted that the MAXQDA software is used for coding the interviews. Finally, the specified codes were categorized and analyzed in the form of factors affecting poverty in the country. Also, in order to show the complex relationships between factors affecting poverty in iran in the form of main and sub-themes, a qualitative dynamic approach and feedback loops were used in the Vensim 6.4E software environment. In this study, an approach is needed that can reflect the relationship of factors affecting poverty in its formation. Therefore, the relationships between the main and sub-themes extracted from the thematic analysis of expert interviews are depicted with a dynamic view. This method is a tool to show cause and effect relationships about a problem in society. This approach maps the relationships of a set of variables involved in a system. The relationship between system variables is displayed using causal loops. Findings In recent decades, despite the fact that the debate on poverty and poverty alleviation strategies has been raising in the world, and in some countries, basic measures have been taken to reduce income poverty and multi-dimensional poverty have taken place, not only has the situation not improved in Iran, but the country is facing huge crises in this field. In this study, the factors affecting poverty in Iran have been presented in the form of four main themes of political, cultural, production and educational structure. Cultural structure: cultural structure is a force that determines, realizes, facilitates and empowers or inhibits, binds or hinders action. Cultural structure identified in the interviews has been classified into two categories: the mental paradigms of actors (people and officials) and the culture of poverty. Political structure: the elements related to the political structure identified among the experts' interviews have had a significant effect on poverty in Iran by reducing economic growth and creating inequality. These elements include: limited access orders, the presence of subordinate institutions in the economy, political isolation, lack of guarantee of property rights, lack of transparency in access to information, lack of freedom of expression in the press, rent, lack of a strong mechanism for monitoring, weak labor unions, government unresponsiveness, weak local government, not believing in law and legislation, and finally, the lack of education in demanding in schools and universities. Educational structure: in relation to the interaction between education and poverty, it can be acknowledged that without adequate education and appropriate for the society, the individual and the society are limited to a poor life. Sen states that inadequate education in itself can be considered a form of poverty in many societies. Production structure: the elements related to the production structure that were extracted from coding are: false beliefs due to unfavorable conditions, weakness in production culture, non-guaranteeing of property rights, political isolation, erosion of social capital, elimination of comparative advantage in production, corrupt monetary and banking system, presence of institutions subordinate to power in the economy, lack of written program in production, centralization in the center of the country and the environment of rentier economy. Discussion and Conclusion Contrary to the opinion of many officials and people of the society, poverty is not a simple and linear problem, but a complex and systemic disease. There is no specific problem in a system and all problems are related. According to the aggregated model and the self-reinforcing causal relationship, to break the causal relationships, planned policies in the form of main and sub-themes are suggested as follows: Ensuring property rights for a large part of society, so that different people are motivated to invest and participate. Proper use of the potentials of each region to create added value. Recovery of international relations